Power supply transient signal analysis for defect-oriented test. - Plusquellic, J. (IEEE Transactions on computer-aided design of integrated circuits and systems)
Transient signal analysis (TSA) is a testing method that is based on the analysis of a set of VDD transient waveforms measured simultaneously at each supply port. Defect detection is performed by applying linear regression analysis to the time or frequency domain representations of these signals. Chip-wide process variation effects introduce signal variations that are correlated across the individual power port measurements. In contrast, defects introduce uncorrelated local variations across these measurements that can be detected as anomalies in the cross-correlation profile derived (using regression analysis) from the power port measurements of defect-free chips. This paper focuses on the application of TSA to the detection of delay faults.